Pyoderma Gangrenosum in an Infant - Soares Martins, Michelle (2016)
Pyoderma gangrenosum is an uncommon cutaneous dermatosis of unknown pathogenesis, included in the group of neutrophilic dermatosis. It is characterized as noninfectious, necrotizing and painful cutaneous ulcers. It affects primarily adults and is rare in children (less than 4%) and with few cases reported in literature of involvement in the age group < 1 year. The diagnosis is usually based on clinical evidence and confirmed with the exclusion of others causes of skin ulcerated lesions. This report describes a case of pyoderma gangrenosum in a 4 months old infant presented with multiple cutaneous ulcers on her buttocks, without any systemic involvement and with rapid and effective response to oral corticosteroid.